2017
DOI: 10.1093/gerona/glx054
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Olfactory Dysfunction in Old Age: A Population-Based Study

Abstract: Background:Olfactory dysfunction (OD) in old age is associated with poor health outcomes. Interrelationships among different correlates of OD can offer insights into the underlying mechanisms, but to date remain understudied.Methods:Odor identification performance and self-reported olfactory functioning were studied in 2,234 people aged 60–90 years, who were free of neurodegenerative disease and enrolled in the Swedish National Study on Aging and Care in Kungsholmen (SNAC-K) study, Stockholm, Sweden. OD was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
80
3
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(98 citation statements)
references
References 49 publications
7
80
3
8
Order By: Relevance
“…Several studies have proposed that age might affect olfactory dysfunction in patient groups . In our study, a subgroup analysis of age revealed the unexpected observation that a smaller age difference (<2 years) between the two groups resulted in a greater olfactory deficit.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Several studies have proposed that age might affect olfactory dysfunction in patient groups . In our study, a subgroup analysis of age revealed the unexpected observation that a smaller age difference (<2 years) between the two groups resulted in a greater olfactory deficit.…”
Section: Discussionmentioning
confidence: 44%
“…Several studies have proposed that age might affect olfactory dysfunction in patient groups. 26,27 In our study, a subgroup analysis of age revealed the unexpected observation that a smaller age difference (<2 years) between the two groups resulted in a greater olfactory deficit. These results indicated that the robust and confirmed difference in olfactory deficits found in our study was not merely due to a decrease in olfactory function due to old age, but rather was related to true deficits in olfaction related to AD pathology (see Supporting Figure 1A in the online version of this article).…”
Section: Discussionmentioning
confidence: 49%
“…In addition to affecting quality of life, loss of sense of smell significantly impacts the inability to recognize harmful smells, such as those of rotten foods, gas, and smoke. The prevalence of smell disorders has been reported at between 1% to 25% in previous studies, whereas hyposmia, defined as a reduced ability to smell, is found in 16% of the general population. The prevalence of anosmia, or the loss of sense of smell, is 5% and that has been shown to vary .…”
Section: Introductionmentioning
confidence: 99%
“…Participants were instructed to freely identify the odor; if they did not provide a response, or responded incorrectly, they were presented with four response alternatives (cued identification). In the present context, a correct response under either response format (free or cued) was considered correct (Seubert et al 2017). Test procedures have been described in more detail elsewhere (Larsson et al 2016).…”
Section: Odor Identificationmentioning
confidence: 99%
“…Olfactory dysfunction is common among healthy old individuals, with prevalence ranging between 15 and 70% depending on sample characteristics and diagnostic criteria Handling Editor: Chandra A. Reynolds 1 3 (Seubert et al 2017;Murphy et al, 2002;Schubert et al, 2012). As olfactory impairments are common, a key challenge is to localize subgroups where such impairments may be especially informative with regard to future cognitive development.…”
Section: Introductionmentioning
confidence: 99%